Recombinant cells in the lung increase with age via de novo recombination events and clonal expansion. (April 2017) - Kimoto, Takafumi; Kay, Jennifer E.; Li, Na; Engelward, Bevin P.
Abstract : Homologous recombination (HR) is a critical DNA repair pathway, which is usually error‐free, but can sometimes lead to cancer‐promoting mutations. Despite the importance of HR as a driver of mutations, the spontaneous frequency of such mutations has proven difficult to study. To gain insight to location, cell type, and subsequent proliferation of mutated cells, we used the Rosa26 Direct Repeat (RaDR) mice for in situ detection and quantification of recombinant cells in the lung. We developed a method for automated enumeration of recombinant cells in lung tissue using the Metafer 4 slide‐scanning platform. The mean spontaneous HR frequencies of the lung tissue in young and aged mice were 2 × 10 −6 and 30 × 10 −6, respectively, which is consistent with our previous reports that mutated cells accumulate with age. In addition, by using the capability of Metafer 4 to mark the position of fluorescent cells, we found that recombinant cells from the aged mice formed clusters in the lung tissue, likely due to clonal expansion of a single mutant cell. The recombinant cells primarily consisted of alveolar epithelial type II or club (previously known as Clara) cells, both of which have the potential to give rise to cancer. This approach to tissue image analysis reveals the location and cell types that have undergone HR. Being able to quantify mutant cells in situ within lung tissue opens doors to studies of exposure‐induced mutations and clonal expansion, giving rise to new opportunities for understanding how genetic and environmental factors cause tumorigenic mutations. Environ. Mol. Mutagen. 58:135–145, 2017. © 2017 Wiley Periodicals, Inc.